Microglia in the aged brain develop a hypoactive molecular phenotype after surgery - Zhuoran Yin; Anna K. Leonard; Carl M. Porto; Zhongcong Xie; Sebastian Silveira; Deborah J. Culley; Oleg Butovsky; Gregory Crosby (Journal of Neuroinflammation)
Abstract Background Microglia, the resident immune cells of the brain, play a crucial role in maintaining homeostasis in the central nervous system (CNS). However, they can also contribute to neurodegeneration through their pro-inflammatory properties and phagocytic functions. Acute post-operative cognitive deficits have been associated with inflammation, and microglia have been implicated primarily based on morphological changes. We investigated the impact of surgery on the microglial transcriptome to test the hypothesis that surgery produces an age-dependent pro-inflammatory phenotype in these cells. Methods Three-to-five and 20-to-22-month-old C57BL/6 mice were anesthetized with isoflurane for an abdominal laparotomy, followed by sacrifice either 6 or 48 h post-surgery. Age-matched controls were exposed to carrier gas. Cytokine concentrations in plasma and brain tissue were evaluated using enzyme-linked immunosorbent assays (ELISA). Iba1+ cell density and morphology were determined by immunohistochemistry. Microglia from both surgically treated mice and age-matched controls were isolated by a well-established fluorescence-activated cell sorting (FACS) protocol. The microglial transcriptome was then analyzed using quantitative polymerase chain reaction (qPCR) and RNA sequencing (RNAseq). Results Surgery induced an elevation in plasma cytokines in both age groups. Notably, increased CCL2 was observed in the brain post-surgery, with a greater change in old compared to young mice. Age, rather than the surgical procedure, increased Iba1 immunoreactivity and the number of Iba1+ cells in the hippocampus. Both qPCR and RNAseq analysis demonstrated suppression of neuroinflammation at 6 h after surgery in microglia isolated from aged mice. A comparative analysis of differentially expressed genes (DEGs) with previously published neurodegenerative microglia phenotype (MGnD), also referred to disease-associated microglia (DAM), revealed that surgery upregulates genes typically downregulated in the context of neurodegenerative diseases. These surgery-induced changes resolved by 48 h post-surgery and only a few DEGs were detected at that time point, indicating that the hypoactive phenotype of microglia is transient. Conclusions While anesthesia and surgery induce pro-inflammatory changes in the plasma and brain of mice, microglia adopt a homeostatic molecular phenotype following surgery. This effect seems to be more pronounced in aged mice and is transient. These results challenge the prevailing assumption that surgery activates microglia in the aged brain.